PROSEDUR ANALISIS KESALAHAN BERBAHASA - -, Dawud (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2008)
An error in language use is an instance of using language in a way whichdiverges from the norms of the target language. Such errors are natural phenomenain the process of language learning. Analyses of such errors have three importantfunctions: a pedagogical function, a methodological function, and a facilitativefunction in a process of language acquisition. Such an analysis is done by goingthrough the procedure of collecting language learners' language samples,identifying the errors, then describing them, and finally explaining them.Keywords: errors in language use, error analysis, contrastive analysis